Penguatan Karakter Siswa dalam Perspektif Kecerdasan Spiritual dan Kecerdasan Emosional di Madrasah Aliyah Negeri 2 Bogor - Ria Rizki Agustini; Maemunah Sa’diyah; Adian Husaini (Universitas Negeri Medan, 2026)
Education not only aims to educate students, but also to build character according to the mandate of Law Number 20 of 2003. However, various problems such as bullying, fights, and low respect for teachers show the need to strengthen character through spiritual and emotional intelligence. This study aims to analyze the character of students, the level of spiritual and emotional intelligence, the relationship between the two and the character, and the magnitude of the influence given to MAN 2 Bogor students. The study uses a quantitative approach with a correlational method through the distribution of questionnaires. The results of the study showed that students' character was in the category of quite good, emotional intelligence was in the category of quite good, and spiritual intelligence was in the good category. In addition, spiritual and emotional intelligence has a strong relationship with the character of students and has an influence of 48% on the formation of the character of MAN 2 Bogor students.